A Dual‐Response Fluorescent Probe Reveals the H2O2‐Induced H2S Biogenesis through a Cystathionine β‐Synthase Pathway. Issue 43 (4th September 2015) - Yi, Long; Wei, Lv; Wang, Runyu; Zhang, Changyu; Zhang, Jie; Tan, Tianwei; Xi, Zhen
Abstract The two signaling molecules H2S and H2O2 play key roles in maintaining intracellular redox homeostasis. The biological relationship between H2O2 and H2S remains largely unknown in redox biology. In this study, we rationally designed and synthesized single‐ and dual‐response fluorescent probes for detecting both H2O2 and H2S in living cells. The dual‐response probe was shown to be capable of mono‐ and dual‐detection of H2O2 and H2S selectively and sensitively. Detailed bioimaging studies based on the probes revealed that both exogenous and endogenous H2O2 could induce H2S biogenesis in living cells. By using gene‐knockdown techniques with bioimaging, the H2S biogenesis was found to be majorly cystathionine β‐synthase (CBS)‐dependent. Our finding shows the first direct evidence on the biological communication between H2O2 (ROS) and H2S (RSS) in vivo.